Legal nature of the contract on the use of electronic money - Петрофанова, Ксенія Романівна (Problems of legality, 2018)
Most scholars studying electronic money, consider them as an economic category, analyzing the advantages and disadvantages of electronic money as a means of payment, leaving out the attention to the question of the legal nature of the contract when using electronic money. Taking into account the fact that the aforementioned agreement is the basis for the obligation to issue, transfer and repay the electronic money, the actual implementation of civil legal analysis of the contract on the use of electronic money is considered. The question of studying the legal nature of the contract on the use of electronic money was devoted to the works of such scholars as A. Isaev, M. Korostelov, V. Loshchylin and others. Along with this, the mentioned problem acquires a new urgency, in connection with the increase of settlements with the use of electronic money. The purpose of the article is to clarify the legal nature and concept of the contract on the use of electronic money. The study of the legal nature of the contract on the use of electronic money is accompanied by the discovery of a large number of theoretical and practical problems and individual discussion issues that have important applied value. This condition is due to the fact that today the civil legal regulation of the circulation of electronic money is in the making. However, it should be noted that the dynamics of the development of relations associated with the use of electronic money, generates significant changes in legislation aimed at regulating such relations. In connection with this, scientific research on this issue will remain relevant for a long time.